2017
DOI: 10.1111/1462-2920.13958
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling causation: complex roles of coral‐associated microorganisms in disease

Abstract: Summary Rapidly changing climate regimes combined with other anthropogenic pressures are implicated in increased disease epizootics among reef building corals, resulting in changing habitat structure. These accumulated stressors directly contribute to disease outbreaks by compromising the coral host immune system, modulating virulence of microbial pathogens and/or disrupting the balance within the microbiome of the holobiont. Disentangling coral disease causation has been challenging, and while progress has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 232 publications
0
58
0
Order By: Relevance
“…However, in both cases, the sponge-associated microbiota shifted from a specific- to a generalist-dominated community in the unhealthy individuals. These findings indicate that, similar to corals [ 207 , 208 ], sponge diseases appear to start with an imbalance of the holobiont which is then followed by opportunistic or polymicrobial infections.…”
Section: Holobiont Responses: Stress Dysbiosis and Acclimatizationmentioning
confidence: 76%
“…However, in both cases, the sponge-associated microbiota shifted from a specific- to a generalist-dominated community in the unhealthy individuals. These findings indicate that, similar to corals [ 207 , 208 ], sponge diseases appear to start with an imbalance of the holobiont which is then followed by opportunistic or polymicrobial infections.…”
Section: Holobiont Responses: Stress Dysbiosis and Acclimatizationmentioning
confidence: 76%
“…Several studies have identified Vibrio spp. (⋎-Proteobacteria ) as causative agents of coral bleaching for multiple coral species and in multiple locations (Ushijima et al, 2014 ; reviewed in Mera and Bourne, 2018 ). Vibrio coralliilyticus ( V. coralliilyticus ) has emeregd as an important bacterial pathogen model for understanding the establishement and propagation of coral disease (Sussman et al, 2008 ; O'Santos et al, 2011 ; Garren et al, 2014 ; Pollock et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding coral disease causation remains challenging as complex interactions exist between causative agents, environment and host 1 , 15 . External factors such as infectious or opportunistic pathogens and environmental stressors may affect a compromised coral holobiont, potentially triggering diseases 15 . In particular, complex interactions have been identified within coral microbial communities driving disease processes 16 .…”
Section: Introductionmentioning
confidence: 99%